Sensitivity of Optimal Control Systems - Atluri, Ratnam Satya (My University, 1966)
The sensitivity of performance to variations in plant parameters is considered for optimal open-loop linear control as well as optimal closed-loop linear control with one or two degrees of freedom. It has been shown that, in general, the sensitivity of performance to finite variations in a plant parameter, is smaller for closedloop optimal control than for the open-loop case.
A second order linear plant has been considered as an example, to further illustrate the theory, which is contrary to some recently published work.
Keywords: Electrical Engineering; Electrical and Computer Engineering; Electrical and Computer Engineering